2006
DOI: 10.1016/j.mito.2006.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Impaired platelet mitochondrial activity in Alzheimer’s disease and mild cognitive impairment

Abstract: Mitochondrial abnormalities are found in Alzheimer's disease (AD), but previous reports haven't examined at-risk groups. In subjects with AD, mild cognitive impairment (MCI), and nondemented aged controls, platelet and lymphocyte mitochondria were isolated and analyzed for Complexes I, III, and IV of the electron transport chain. Western blots were used to control for differential enrichment of samples. Results demonstrated significant declines in Complexes III and IV in AD, and a significant decline in Comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
101
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(115 citation statements)
references
References 51 publications
(57 reference statements)
10
101
1
Order By: Relevance
“…activity caused increased lipid peroxidation, in agreement with increasing evidence implicating C.O. inhibition and oxidative damage as neurodegenerative mechanisms in MCI and AD Benzi and Moretti, 1995;Blass et al, 2002;Mielke and Lyketsos, 2006;Reddy and Beal, 2005;Valla et al, 2001;Valla et al, 2006). The PCC may be a metabolically vulnerable brain region.…”
Section: Discussionsupporting
confidence: 86%
“…activity caused increased lipid peroxidation, in agreement with increasing evidence implicating C.O. inhibition and oxidative damage as neurodegenerative mechanisms in MCI and AD Benzi and Moretti, 1995;Blass et al, 2002;Mielke and Lyketsos, 2006;Reddy and Beal, 2005;Valla et al, 2001;Valla et al, 2006). The PCC may be a metabolically vulnerable brain region.…”
Section: Discussionsupporting
confidence: 86%
“…The AD COX defect in this study was identified through studies of platelet mitochondria. A similar finding was subsequently demonstrated in independent studies of brain, platelet, and fibroblast mitochondria (24, 31, 40, 62,144,165,176,189,204,205,240,280,281,284,292). Some researchers attributed the COX activity reduction to declining COX protein or COX subunit mRNA levels (42,43,111,145).…”
Section: Mitochondria Are Increasingly Implicated In Ad and Ad Modelssupporting
confidence: 63%
“…This notion is supported by an extensive literature which reports that AD is characterized by reduced cerebral energy metabolism (8), impaired activities of the tricarboxylic acid cycle enzymes (25,121,162), and defects in the mitochondrial ETC (21,32,45,146,96,193). The most consistent defect at ETC level is the decline in cytochrome c oxidase (COX) activity, an effect that is positively correlated with Ab concentration, as determined by in vitro studies (30).…”
Section: Oxidative Stress In the Aging Brainmentioning
confidence: 83%